Lived experiences of recovery among persons with schizophrenia in Thailand: A qualitative study - Jundeekrayom, Surada; Soonthornchaiya, Rangsiman; King, Beth (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Schizophrenia is a chronic and disabling mental illness that presents a significant public health challenge worldwide. It affects multiple aspects of an individual’s life, often resulting in poor health outcomes, disability, and impaired daily functioning. With advances in ongoing care and relapse prevention, the focus of treatment has shifted toward promoting remission and personal recovery. However, few studies have explored the lived experiences of recovery among individuals with schizophrenia in Southeast Asia, especially within the Thai cultural context. Objective: This study aimed to explore the lived experiences of recovery among individuals with schizophrenia in Northeastern Thailand. Methods: A qualitative hermeneutic phenomenological approach was used. Twenty-three community-dwelling individuals in the recovery phase of schizophrenia were purposively selected. Data were collected through in-depth, face-to-face interviews between December 2021 and June 2022. Interviews were transcribed verbatim and analyzed using hermeneutic analysis to identify underlying themes. Results: Participants described recovery as a process of “bringing life back to normal living.” Two interrelated themes emerged: (1) Being normal through social connectedness, and (2) Living a happy and meaningful life. These themes highlight the importance of social roles, community acceptance, emotional well-being, and culturally rooted definitions of normalcy in the recovery process. Conclusion: Recovery from schizophrenia extends beyond symptom control to include social reintegration and the restoration of purpose and well-being. Psychiatric nurses play a vital role in supporting this process by developing interventions that transcend biomedical treatment, fostering social connectedness, personal meaning, and emotional resilience. Culturally sensitive, holistic care strategies are essential to help individuals achieve their own definitions of a fulfilling and “normal” life.